Planning for pandemic resilience: COVID-19 experience from urban slums in Khulna, Bangladesh - Salma Akter; Sheikh Serajul Hakim; Md. Saydur Rahman (Journal of Urban Management, 2021)
COVID-19 worsened urban slum dwellers' pre-existing vulnerabilities. Maintaining WHO-suggested physical distancing/isolation made planning more challenging in slums. The scenarios hint at the urgency to investigate whether these resource-scarce communities - already susceptible to climate change, poverty, health services, infrastructure, and space constraints, could build resilience against COVID-19. What lack of resources/assets made communities vulnerable there, and what adaptation measures were taken? What planning/management practices were adopted there, and to what extent could WHO's IPC guidelines (on transmission prevention and control) be followed? Findings show that pre-COVID economic, infrastructural, and health-related issues had affected slum dwellers' COVID-time vulnerabilities. While poor infrastructure and sanitation, informal employment, livelihood diversity, superstition, and comorbidities remained the key 'internal' issues, lack of institutional preparedness and safety-net programs, discontinued municipal services and inaccessible/untrustworthy healthcare services and corruption/bias/non-coordination in beneficiary selection remained the key 'external' issues. Information sharing, openness to pandemic knowledge, and active participation in awareness/training programs have been the most adopted measures. Aid schemes, despite criticisms, saved dwellers from starvation. Therefore, this proved to be a critical coping element. However, NGOs systematic monetary aid gave dwellers the most flexibility in spending. On top, NGOs proved to be the most vital external stakeholder in all sectors except for built environment/planning. To increase adaptive capacity, scopes remain in maximizing the use of community infrastructure in future events. Simultaneously, spatial aspects, alongside the non-spatial, seemed crucial in tackling complex poverty profiles, resource-scarcity, and vulnerabilities of slums. Findings are based on NGO BRAC's existing dataset and fieldwork between April-August 2020 on 29 slums in Khulna, Bangladesh, using a qualitative methodology. The study contributes to a growing body of knowledge and practice on resilient planning for COVID-19 (and similar future pandemics), especially for slums, while addressing its overlooked spatial dimensions.
Keywords: 710; COVID-19; Pandemic; Vulnerability/adaptation; Resilience; Urban slums; Khulna